In Vitro Activity of Rifampicin and Verapamil Combination in Multidrug-Resistant Mycobacterium tuberculosis - Demitto, Fernanda de Oliveira; do Amaral, Renata Claro Ribeiro; Maltempe, Flaviane Granero; Siqueira, Vera Lúcia Dias; Scodro, Regiane Bertin de Lima; Lopes, Mariana Aparecida; Caleffi-Ferracioli, Katiany R.; Canezin, Pedro Henrique; Cardoso, Rosilene Fressatti (PLOS ONE, 2015)
The aim of the present study was to evaluate the effect of the combination of rifampicin (RIF) and verapamil (VP) against the Mycobacterium tuberculosis H37Rv reference strain and six multidrug-resistant (MDR) M. tuberculosis clinical isolates by determining Time-Kill Curves and the ability to efflux drug by fluorometry. The RIF+VP combination showed synergism in one MDR clinical isolate. For the other five MDR clinical isolates, the drug combination showed no interaction. The MDR clinical isolate had lower ethidium bromide (EtBr) accumulation when exposed to the RIF+VP combination, compared with RIF and VP exposure alone. The other MDR clinical isolates showed no significant difference in EtBr accumulation. These results suggest greater efflux action in one of the MDR clinical isolates compared with the M. tuberculosis H37Rv reference strain. The other five MDR isolates may have additional mechanisms of drug resistance to RIF. The use of the RIF+VP combination made one MDR bacillus more susceptible to RIF probably by inhibiting efflux pumps, and this combination therapy, in some cases, may contribute to a reduction of resistance to RIF in M. tuberculosis.